Electromagnetically-vibrated solid-phase microextraction for analysis of aqueous-miscible organic compound transport in soil columns. (January 2021) - Joo, Jin Chul; Shackelford, Charles D.; Reardon, Kenneth F.; Lee, Won Tae
Abstract: Current methods of sampling pore water from soil columns to determine solute concentrations are slow and require relatively large volumes. Accordingly, an electromagnetically-vibrated (EMV) solid-phase microextraction (SPME) device was evaluated for determining temporal and spatial distributions of solute pore-water concentrations (solute concentration profiles) for four organic compounds, two polar (2-hexanone, 2, 4-dimethyl phenol) and two nonpolar (toluene, 1, 4-dichlorobenzene), in columns packed with simulated aquifer sands with different fractions of organic carbon. In batch equilibrium extraction tests, the equilibrium extraction time of the organic compounds in aqueous mixtures decreased from 30 to less than 10 min as the frequency of electromagnetic vibration increased from zero to 250 Hz. Mixture effects were not statistically significant ( p > 0.05) in the extraction process using EMV SPME. Comparisons of the solute concentration profiles within the soil columns at different elapsed times measured by pore-water samples and in situ EMV SPME extractions revealed both methods were equally effective. However, EMV SPME extraction removed no solution volume and only 0.6–14% of the solute mass removed by the pore-water sample collections, substantially minimizing disturbances to solute transport and fate. Thus, the equilibrium extraction-based calibration method using EMV SPME offers an effective approach for rapidly and accurately determining solute concentration profiles in column tests with negligible solute mass loss and minimal solution flow disturbance. Highlights: Electromagnetically-vibrated (EMV) solid-phase microextraction (SPME) was used to determine solute concentration profiles. Electromagnetic vibration of SPME at 250 Hz for 10 min provided the best performance. In-situ EMV SPME extraction device effectively determined solute concentration profiles in soil columns. Negligible solute mass loss and disturbance of solute transport was observed with in-situ EMV SPME extraction. Equilibrium extraction-based EMV SPME can replace pore-water sampling in soil columns.